Purwakanthi dalam Pertunjukan Wayang Kulit Purwa - Tatik Harpawati (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2007)
This article will study the exploiting of language medium to get the certain effect of catur in the puppet plays. One of the language mediums that can be exploited in the form of the usage of sound language related to rime rhythm. The study of rime or purwakanthi involves purwakanthi guru swara, basa and sastra indicate that there is an existence of sound similarity at nearby words. It can strengthen the compability of rhythm and create the atmosphere and also certain impression. It can be happened because of contact of sharpened hearing sense that will be able to feel the beauty, compatibility in sound which emergency successive and oreder.Key words : purwakanthi, catur, puppet plays